Usurpación y religión en el s. IV d. de C. Paganismo, cristianismo y legitimación política - Escribano Paño, María Victoria (Antigüedad y cristianismo: Revista de Estudios sobre Antigüedad Tardía, 1990)
The first part of this study analyses the reasons underlying the identification of the usurper with the ideological figure of the tyrant, and also the place occupied by the term «inipiety» amongst the infamous characteristics peculiar to the typical portrait of this figure since its genesis in the framework of the Atenas post-Clistenical. In the second part, with these theoretical suppositions as a background, the author explains and documents the utilization of the religion as a means to legitimate the power of Maximus obtained by the force of arms, and whose intervention in the Priscillian certamen complied to his purpose of justifying before the Apostolic See and the Court of Constantiople where he seeked to be recognized as the Emperor worthy of the PARS OCCIDENTIS.